(untitled) (International journal of medical sciences, 2026)
Surgery is the primary treatment for complicated colon cancer. Complicated left colon cancers are often accompanied by acute intestinal obstruction, inflammatory infiltrates, perforation, and peritonitis, requiring emergency surgery. Traditional Hartmann colostomy procedures do not always restore intestinal continuity and are associated with a decrease in patients' quality of life. This article presents experience performing subtotal colectomy with ileosigmoid and ileorectal anastomoses for complicated left colon cancer. Between 2012 and 2023, subtotal colectomy for complicated left colon tumors was performed in 37 patients. The patients ranged in age from 40 to 80 years. This method has been shown to restore intestinal continuity, reduce the incidence of colostomies, and improve postoperative outcomes.